2011
DOI: 10.1080/09603107.2011.570711
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal variables and bond spreads – evidence from Eastern European countries and Turkey

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 24 publications
0
21
0
2
Order By: Relevance
“…Using country regressions, Arora and Cerisola (2001) and Nickel et al (2009) find that while global factors are important drivers of spreads in almost every country, the significance of fundamentals differs across countries. Similarly, Ebner (2009) shows that the effect and importance of country-specific factors varies across countries and concludes that external risk aversion is "the single most important explanatory factor" of spreads.…”
Section: Related Literaturementioning
confidence: 99%
“…Using country regressions, Arora and Cerisola (2001) and Nickel et al (2009) find that while global factors are important drivers of spreads in almost every country, the significance of fundamentals differs across countries. Similarly, Ebner (2009) shows that the effect and importance of country-specific factors varies across countries and concludes that external risk aversion is "the single most important explanatory factor" of spreads.…”
Section: Related Literaturementioning
confidence: 99%
“…They did not model this effect explicitly, but concluded that it was the result of policy anchors brought by the EU accession process. Nickel et al (2009) focused their analysis on the impact of fi scal variables on bond spreads. They used forecasted values of macroeconomic variables to capture market expectations, and showed that the fi scal defi cit had a signifi cant infl uence on bond spreads.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yet another part of this research has focused on the determinants -including the fiscal ones -of the long-term yield spreads between new European Union countries and other European states and benchmarks such as the US or the German bonds (see e.g. Nickel, Rother and Rülke, 2009;Alexopolou, Bunda and Ferrando, 2009 In addition, Ehrmann, Fratzscher, Gurkaynak and Swanson (forthcoming), used daily yields of maturities between two and ten years to study the convergence of the shape of the yield curves of Italy and Spain with those of France and Germany after the EMU, looking at the first (level) and second (slope) principal components of the yield curve. However, they have not considered the very short-end maturities and did not explicitly relate the behaviour of the yield curves to fiscal variables.…”
Section: Ecb Working Paper Series No 1276mentioning
confidence: 99%